Brexit and the Anglosphere: an intra-industry trade opportunity for India? - Calderón-Vázquez, Francisco José; Chandnani Sukhwani, V.; Podadera-Rivera, Pablo (Centre for European Studies, 2020)
The present paper outlines a functionalist approach to the complex “Brexit” phenomenon, exploring those opportunities that can be derived of it for third countries, unaware of the upheaval European scenario, as could be the case of India. In pro-Brexit approaches, The Indian Union appears as one of the most important countries of the Anglosphere area, particularly significant for a future focus of the brand-new “Global UK”, a relevant global partner in economic, trade & investment aspects. Due to the denominated “Intra-Industry Trade” (IIT), instrumented over the Global Value Chains (GVCs), which possibly constitutes one of the fundamental explanatory elements of the Global World, we have proposed an analysis of the UKIndia relations from the IIT & GVCs perspective. Therefore, in our work, we do an analysis of the evolution, situation and perspectives of this kind of trade, especially for its three main sectors: Apparel & Footwear, Electronics and Transport Vehicles.
https://ejes.uaic.ro/about_EJES.htm#xl_open
Keywords: Brexit - Aspectos económicos; UK; India; Intra-industry trade; Global value chains